The demo-economic models approach in regional analysis: An application for the projection of regional population of Greece - Rontos, Konstantinos (SPOUDAI Journal of Economics and Business, 2009)
The aim of this article is to predict the total and regional population of Greece for the year 2011, using a recently developed approach, which is considered to be more realistic than pure demographic models or gravity models. This approach, known as “Demo-economic Models”, is of a dynamic nature and presupposes that there is interaction between the demographic and economic factor. In this procedure, internal migration is considered to constitute the connecting link between economic development and population shifts. Application of this method resulted in evidence that, despite the relevant halt in the urbanization progress during the past years in Greece, Greek population will still be unequally distributed during the first decade of the twenty-first century, with major concentrations in the two biggest metropolitan areas of Athens and Thessaloniki; in fact, among other reasons, these regions seem to attract most of foreign immigrants, too. Additionally, total population of Greece is estimated to slightly increase by 3.8 % in 2011, in comparison to 2001. JEL Classifications: R23, C31